The displaced : refugee writers on refugee lives - Nguyen, Viet Thanh, 1971-; Abani, Chris; Azam, Joseph; Bezmozgis, David, 1973-; Bhutto, Fatima, 1982-; Bui, Thi.; Dorfman, Ariel; Golinkin, Lev.; Grande, Reyna; Hadero, Meron, 1978-; Hemon, Aleksandar, 1964-; Kertes, Joseph, 1951- (New York : Abrams Press, 2019)
Pulitzer Prize-winning author Viet Thanh Nguyen, himself a refugee, brings together a host of prominent refugee writers from around the world to explore and illuminate their experiences. Poignant and insightful, this collection of essays reveals moments of uncertainty, resilience in the face of trauma, and a reimagining of identity. The Displaced is a powerful look at what it means to be forced to leave home and find a place of refuge.
Introduction / Viet Thanh Nguyen -- The road / Chris Abani -- Last, first, middle / Joseph Azam -- Common story / David Bezmozgis -- Flesh and sand / Fatima Bhutto -- Perspective and what gets lost / Thi Bui -- How succulent food defeated Trump's wall before it has been built / Ariel Dorfman -- Guests of the Holy Roman Empress Maria Theresa / Lev Golinkin -- The parent who stays / Reyna Grande -- To walk in their shoes / Meron Hadero -- God's fate / Aleksandar Hemon -- Second country / Joseph Kertes -- 13 ways of being an immigrant / Porochista Khakpour -- Refugees and exiles / Marina Lewycka -- This is what the journey does / Maaza Mengiste -- The ungrateful refugee / Dina Nayeri -- Am I a refugee? / Raja Shehadeh -- A refugee again / Vu Tran -- New lands, new selves / Novuyo Rosa Tshuma -- Refugee children : the Yang warriors / Kao Kalia Yang.
Originally published: 2018. Contains new chapter: The road / Chris Abani.
Keywords: Refugees